Comparison of Trauma Scoring Ability to Predict Survival Rate in Countries with Low to Middle-Income - Servasius Ratu Banin; Yuyun Yueniwati; Yulian Wiji Utami (International Journal of Science and Society, 2020)
The use of trauma scoring in the hospital is very important because it has a significant impact both clinically and economically. However, not all trauma scoring that we know today is suitable for use in low to middle-income countries or applied in hospitals with limited resources. The purpose of compiling a systematic review is to identify which trauma scoring is most appropriate for use in low to middle-income countries. This systematic review was built by identifying scientific articles published between 2010-2019. Search for articles was carried out with the keywords "Trauma Scoring" and "Low And Middle-Income Country". The search was carried out with the help of databases including ProQuest, science direct, and PubMed and SpringerLink. From this search, we found 3802 articles. Furthermore, the 3802 articles were screened with the help of PRISMA flow diagrams and criticized with the JBI tool. After that, 9 articles relevant to the research question were obtained to be analyzed into a systematic review. The results showed that 4 articles were stating that the Kampala Trauma Score (KTS) had a higher AUC ROC value when compared to another trauma scoring. Also, in these four articles, KTS had the lowest AIC score. Thus, it can be concluded that VCT is trauma scoring which is most suitable to be applied in low to middle-income countries or hospitals in rural areas with limited resources.